Marketing strategy of online education expanding to Czech republic on the example of Education Academy Rokus s.r.o. - Kušnírová, Ema Bianka; Bahles, Michael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Bachelor thesis Marketing strategy of online education expanding to the Czech Republic on the example of Education Academy Rokus s.r.o. deals with the expansion of the Slovak company Rokus s.r.o. with its Education Academy to the Czech market of online education. This research aims to develop a marketing strategy for this expansion while considering the cultural, regulatory, and competitive aspects of the Czech Republic. The theoretical framework of this thesis explains the analysis, such as PESTEL, SWOT, STP marketing strategy, or marketing mix. Those analyses help to evaluate the external and internal factors that influence the marketing strategy of Education Academy Rokus s.r.o. On the other hand, expansion and the foreign market bring intense competition, limited webinar topics, and the need for local content and expanded operational capacity. This thesis proposes several tools for a successful expansion and integration of the company Education Academy Rokus s.r.o. in the Czech educational market.
Vedoucí práce: Michael Bahles
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses